EXERCISE RINGAN MENURUNKAN TEKANAN DARAH PADA PENDERITA HIPERTENSI - rina loriana; ismansyah ismansyah (MNJ (Mahakam Nursing Journal), 2017)
This study is very helpful aerobic exercise against blood pressure in people with hypertension. This study used pre group and post randomized block design. The number of samples in this study were 30 respondents. Pre test performed before aerobic exercise. Intervention was administered for 10 weeks and then performed post test. Data were analyzed by using Wilcoxon test. The result showed that the average systolic blood pressure dropped after 10 weeks aerobic exercise was 10,71% with mean of sistol blood pressure drop 17 mmHg with p value = 0.000 <0,05, mean the decrease of diastole blood pressure equal to 9,31% With mean diastole blood pressure 9 mmHg with p value = 0.000 <0,05. Aerobic exercise can lower blood pressure sistole and diastole in people with hypertension done regularly. Keywords: exercise, hypertension